Pengaruh Transparansi, Partisipasi Masyarakat, Kompetensi Aparatur, Dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Keuangan Dana Desa - Devi, Atshari Sri; Ahmad, Afridian Wirahadi; Sriyunianti, Fera (Journal of Applied Accounting And Business, 2024)
This research aims to examine and analyze the impact of transparency, community involvement, apparatus competence, and internal control systems on the accountability of village fund financial management in Pariaman City. Employing a quantitative approach, the study population comprised village officials from 55 villages in Pariaman City. A purposive sampling technique was utilized to select the sample, focusing on village heads, village secretaries, and finance clerks with a minimum of one year of service, resulting in a sample size of 165 respondents. Data was gathered through questionnaires distributed to the village officials and subsequently analyzed using the SPSS v.26 software. The findings revealed that transparency, apparatus competence, and internal control systems individually influenced the accountability of village fund financial management, whereas community participation did not. However, when considered collectively, transparency, community participation, apparatus competence, and internal control systems were found to have a significant effect on the accountability of village fund financial management.